The Relationship Form Fish Farmer of Softcrab (Scylla serrata) With Employers In The Village of Tangkahan Durian, West Berandan Subdistrict, Langkat Regency, North Sumatera Province - Nababan, Peronika; Hendri, Ridar; ', Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Social interaction is the base of the social process, or social process on society as a consequence of social interaction (social relationship form). The Village of Tangkahan Durian, West Berandan Subdistrict is one of the potential region for softcrab cultivation. The problems faced by the fish farmer is the lack of availability of crab seed than the cultivator necessity make the crab seed price becomes very expensive, otherwise the big industrialist (employers) dominate the crab seed then the small cultivator doesn’t get the crab seed on time.The relationship of fish farmer (client) with employers (patron) is hard to be separated because this relation is neccesary on both sides. The relationship of fish farmer with employers have negative and positive effect. Economic relationship are formed from economic activity include production input supplying and cultivating product marketing and financial loan. Social relationship was appear from interaction between the fish farmer and employers in financial loan, production input loan and cultivating product marketing. The fish farmer always give priority on the interaction when solve a problem directly or face to face. Personal relationship is a direct or intensif relations between the cultivators and employers, which cause the relations between the cultivators and employer are not only for the profit motives, as the other hard there are chemistry between fish farmer and employers.Keywords: Patron-Client, Economic Relationship, Social Relationship, Personal Relationship.